Health status of young construction workers in the Global South: The case of Ghana. (April 2022) - Frimpong, Samuel; Bemah Antwi, Abena; Yosia Sunindijo, Riza; Changxin Wang, Cynthia; Ampratwum, Godslove; Dansoh, Ayirebi; Seiwaa Boateng, Ethel; Antwi Hagan, Jonathan; Annor Mensah, Peter
Highlights: There is a high prevalence of musculoskeletal disorders, skin problems, and migraine. There is a high prevalence of substance abuse disorder and sleep problems. Age sub-group difference has no significant influence on poor mental health status. The level of some mental conditions are significantly influenced by work location. Abstract: Poor health is increasing significantly among young construction workers worldwide. However, the case of young workers in the Global South is not well understood. We sought to identify the physical and mental conditions that affect young workers and measure their levels of prevalence. We also sought to analyze the influence of age and work location on young workers' work-related mental health. Using a sequential exploratory mixed methods approach, a survey instrument was first developed through interviews and a focus group, and subsequently used to measure a range of physical and mental health conditions among 445 young workers in Ghana's construction industry. Prevalence levels and sub-group differences were analyzed using descriptive statistics and multivariate analyses respectively. The results indicated a high prevalence of work-related musculoskeletal disorders and skin problems. There was also a high prevalence of the work-related substance abuse disorder, sleep problems, schizophrenia, and mania. No significant differences in the levels of work-related mental health problems were exhibited among different youth age sub-groups. Work location however accounted for significant differences in the levels of substance abuse disorder, sleep problems, anxiety disorder, and somatic symptoms exhibited. The findings of this study can be used to promote an awareness of the poor health of young construction workers, and can help policymakers, health practitioners, and researchers in low resource settings to know the specific health issues that ought to be prioritized.